Семантическое моделирование для построения онтологий предметных областей - Волошина, Н. А.; Нестерчук, Ю. Э. (ХНУРЭ, 2008)
The given work is dedicated to modern development in the field of information technology. As follows creation ontology by means of semantic modeling. As examples were explored such application domains as profession Intellectual systems decision making of the Kharkiv national university of radioelectronics and requirements of the employers in sphere Information technology. It is described stages of the building ontology and their main advantage.
Keywords: семантическое моделирование; построение онтологий предметных областей